2019
DOI: 10.1186/s12870-019-1839-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptomic analysis reveals genetic divergence and domestication genes in Diospyros

Abstract: Background Persimmon ( Diospyros kaki ) is the most economically cultivated species belonging to the genus Diospyros . However, little is known about the interspecific diversity and mechanism of domestication, partly due to the lack of genomic information that is available for closely related species of D. kaki (DK). Here, we performed transcriptome sequencing on nine samples, including DK, a variety of DK and seven c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 54 publications
0
8
0
1
Order By: Relevance
“…To our knowledge, breeding practice has a greater impact on reducing the level of genetic diversity compared with domestication, resulting in lower genetic diversity in cultivars than that in wild varieties [ 50 52 ]. In this study, we found that the wild types of MO were significantly different from cultivated types not only in morphological traits, chemical compositions, but also in genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, breeding practice has a greater impact on reducing the level of genetic diversity compared with domestication, resulting in lower genetic diversity in cultivars than that in wild varieties [ 50 52 ]. In this study, we found that the wild types of MO were significantly different from cultivated types not only in morphological traits, chemical compositions, but also in genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Methods based on the fraction of synonymous substitutions per synonymous site (Ks) between a given pair of orthologues or paralogues can be employed to estimate the time since divergence or duplication (e.gGuan et al, 2019; Lynch & Conery, 2000). This methodology is now widely applied to infer interspecific relationships and whole‐genome duplications (WGDs) at genome or transcriptome level (Yang et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Persimmon (Diospyros kaki) is regarded to originate from China [1] and is predominantly cultivated in East Asia, including China, Japan, and Korea. China, which has the largest area and production harvest in the world, produces 3.427 million tons, accounting for 75% among all the countries (The Food and Agriculture Organization of the United Nations, FAO, 2021).…”
Section: Introductionmentioning
confidence: 99%